Mushrooms as functional foods - Győrfi, J. (International Journal of Horticultural Science, 2010)
In this study I compared the nutritional composition of the commonly consumed fruits and vegetables with three of the most important cultivated mushrooms: white button mushroom (Agaricus bisporus LANGE/IMBACH), oyster mushroom (Pleurotus spp. JACQ. P. KUMM.) and shiitake (Lentinula edodes BERKELY/PEGLER). I compared the energy content and some mineral values (sodium, potassium, calcium, magnesium and selenium), as these play a major role in the nutritional value of mushrooms. The focus was on the vitamin B group and the vitamin D content in mushrooms, which is especially important due to the fact that fruits and vegetables do not contain this vitamin. Nowadays one of the main research and experimental topic is finding possible ways for enhancing the vitamin D content in cultivated mushrooms by UV-light. The Corvinus University of Budapest is running a project in this research area as well. Based on the data presented in this study we can say that mushrooms and therefore the cultivated mushrooms have an honourable place within the group of functional foods.